-3(-x+5)+20=-10(x-3)+4

Simple and best practice solution for -3(-x+5)+20=-10(x-3)+4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3(-x+5)+20=-10(x-3)+4 equation:



-3(-x+5)+20=-10(x-3)+4
We move all terms to the left:
-3(-x+5)+20-(-10(x-3)+4)=0
We add all the numbers together, and all the variables
-3(-1x+5)-(-10(x-3)+4)+20=0
We multiply parentheses
3x-(-10(x-3)+4)-15+20=0
We calculate terms in parentheses: -(-10(x-3)+4), so:
-10(x-3)+4
We multiply parentheses
-10x+30+4
We add all the numbers together, and all the variables
-10x+34
Back to the equation:
-(-10x+34)
We add all the numbers together, and all the variables
3x-(-10x+34)+5=0
We get rid of parentheses
3x+10x-34+5=0
We add all the numbers together, and all the variables
13x-29=0
We move all terms containing x to the left, all other terms to the right
13x=29
x=29/13
x=2+3/13

See similar equations:

| 1400=14(60+x)+x | | 1-0.4^x=0.9 | | x/9+3=1 | | 2(x-3)-3(2x+1)=3 | | 7x+40=9x-56 | | 5x-3=3x+12 | | 1.07^x=100 | | 13=4-n | | -2x+1=-4x+7 | | a*2+5=1 | | -2x+1=-4x-6 | | (D^3+4D^2+D-6)y=0 | | 2l/5=5/2 | | 12/3a-6=41/3a-10 | | 12/3a-6=41/3-10 | | 2x*23+19*32=32x*2+30-64 | | 10p/4=20 | | x*0,92=2000 | | 3=4(p-5) | | 2x^2-2x+6=2x+13 | | 3x-13=(-4) | | -4.2x+20=3.5x-33.9 | | -3x+7x=x+15 | | 4x-(x+5)=3+(x-2) | | x-4=-2x-8 | | f+93=8 | | x-0.5=-2x+1 | | 18x-30=-12x+57 | | 9x+4x=3x+25 | | 36n-4=35n+56 | | -4x+5=x+20 | | 14x+7=13x+8 |

Equations solver categories